Application of Augmented Reality Module for Alkane Derivatives to Improve Students' Spatial Ability and Mastery of Concepts - Irvan Permana*; Eni Nuraeni; Indarini Dwi Pursitasari; Yuyun Yulianti (Universitas Syiah Kuala, 2023)
Chemistry learning, which includes three levels of representation (macroscopic, sub-microscopic, and symbolic), can shape students' mental models of chemistry. The augmented reality module for alkane derivatives (ARMAD) was developed and implemented to improve students' spatial abilities and mastery of concepts through understanding the three levels of chemical representation. The one-group pre-test and post-test design was implemented with 60 students as participants in a senior high school in Sukabumi, West Java. Spatial ability was measured using five multiple-choice questions and three essay questions for visual-spatial, spatial orientation, and spatial relationships. Concept mastery data was collected using 20 multiple-choice questions. Improved spatial ability and concept mastery were calculated using the normalized-gain test and the Wilcoxon test. The mean score of N-gain spatial ability is in the high category with a score of 0.87 and in the medium category for mastering the concept of alkanes with a score of 0.59. The results of the Wilcoxon test on spatial ability data and mastery of concepts showed that there is a significant difference